The Effectiveness of Using Pictionary Game in Teaching Vocabulary at Junior High School Level - Farma, Nicky Shiela Indira; Candraloka, Olyvia Revalita (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2025)
The objective of this research is to evaluate the impact of Pictionary activities as a pedagogical tool for vocabulary acquisition among middle school learners. The investigative approach employed a quasi-experimental framework involving fifty-eight motivated seventh-grade pupils from MTs Al-Muttaqin Rengging, who were systematically allocated into treatment and comparison cohorts. Information gathering was conducted using initial and final assessments consisting of multiple-choice vocabulary items to monitor learners' academic development precisely. The treatment cohort experienced instruction via dynamic and entertaining Pictionary activities, whereas the comparison cohort followed traditional pedagogical approaches throughout six instructional sessions. The results showed a significant difference between the groups (p = 0.000 < 0.05), with the experimental group's average score (88.50) considerably higher than that of the control group (70.73). Both groups experienced significant improvement, but the experimental group showed greater overall improvement. The conclusion of the study clearly proves that the Pictionary game is significantly more effective than conventional methods in improving students' vocabulary mastery.